Conditions of construction of the system of digital transport and logistics in the management of competitiveness - D. R. Abdyusheva; A. O. Merenkov; A. A. Stepanov (Управление)
Recently, the issue of the development of automation systems in transport is again becoming topical. Note that the first developments in the field of automated control systems (ACS) date back to the mid-20th century, when cybernetics was developing in the USSR. Over time, automation elements have developed in aviation, road and rail transport. However, the level of development of scientific and technological progress allowed only after many years to return to this issue at a qualitatively new level. The next stage in the development of technologies involves the development of elements of artificial intelligence (digitalization) in many branches of the real sector of the economy. The evolution of information technologies allowed companies to put into practice the concept of a marketing (customer-oriented approach). At present, taking into account the opinion of consumers, providing a service of a qualitatively different level, the first factor of ensuring the competitiveness of the company, advantageously emphasizing its position in the market. The purpose of the study is to study the conditions for the formation of the system «digital» transport and logistics. The tasks that determined the course of scientific developments were: to determine the basic principles that are characteristic of the «digital economy» in freight forwarding and logistic services, to identify the main tasks and conditions for the formation of a system of «digital» transport and logistics. “ As the research results, the following provisions should be singled out: the authors specify the basic conditions for the digitization of transport and logistics, identify the necessary conditions, and determine the sufficient conditions for the functioning of this system, taking into account the territorial features of Russia. The authors revealed the main advantages of digital transport development for the participants of the transportation process. The article highlights the role of modern technologies in the process of implementing the principles of a client-oriented approach to transport, which contributes to the improvement of the quality of work of companies in the sphere of freight forwarding and logistics services.